Adequacy of legislation in protecting the rights of muslim women against spousal violence in Malaysia - Che Soh @ Yusoff, Roslina; Abdul Hak, Nora; Ibrahim, Norliah (INSI Publications, 2012)
Violence against women occurs in all countries and transcends social, economic, religious, and cultural groups. One of the most common forms of violence against women is violence by their husbands or other intimate male partners. Over the past two decades, violence by an intimate partner has been identified throughout the world as a serious physical and mental health concern. In the Muslim community, spousal violence has become one of the main issues of concern due to different interpretations of Islamic teaching on gender roles between men and women within varying historical and cultural contexts. Misinterpretation of the Qur’anic injunctions within the cultural context of some Muslim communities resulted in the justification of the men’s abusive acts towards their spouses. In Malaysia, various laws have been enacted to curb the current problem of domestic violence including spousal violence. This paper seeks to examine the rights of Muslim women in Malaysia in particular, against spousal violence under the Syariah (In Malay language, Shari‘ah is known as Syariah) and the Malaysian Laws and discuss to what extent these laws are adequate in controlling the problem of spousal violence in Malaysia. The paper also briefly highlights the issue of marital rape in Islam and whether or not it should be classified as a form of spousal violence. Finally, the paper discusses some possible recommendations as to the relevant legislation and other legal measures that may spur improvement to the present situation in reducing the number of spousal violence cases in the country.